Modern Accelerator Technologies for Geographic Information Science - Shi, Xuan.; Kindratenko, Volodymyr.; Yang, Chaowei. (Springer US : Imprint: Springer, 2013)
This book explores the impact of augmenting novel architectural designs with hardware<U+0010>based application accelerators. The text covers comprehensive aspects of the applications in Geographic Information Science, remote sensing and deploying Modern Accelerator Technologies (MAT) for geospatial simulations and spatiotemporal analytics. MAT in GIS applications, MAT in remotely sensed data processing and analysis, heterogeneous processors, many-core and highly multi-threaded processors and general purpose processors are also presented. This book includes case studies and closes with a chapter on future trends. Modern Accelerator Technologies for GIS is a reference book for practitioners and researchers working in geographical information systems and related fields. Advanced-level students in geography, computational science, computer science and engineering will also find this book useful.